2018
DOI: 10.1016/j.ijid.2018.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Transplant tourism and invasive fungal infection

Abstract: This is the largest single-center study on commercial RTX reporting the highest number of patients with IFI acquired over a relatively short period of time. Aspergillus spp were the main culprit fungi, with no Candida spp being isolated. A high index of suspicion might be the most reasonable means to reduce the possible very poor outcomes. Improving legal transplant programs and strengthening the associated laws could prevent commercial transplant tourism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Cosmetic surgeries such as; abdominoplasty, liposuction and breast augmentation (13,68,78-87,69,88-91,70-73,75-77). Organ transplantation complications were reported in ve studies (97)(98)(99)(100)(101). Similarly, bariatric surgery complications were reported in ve studies (92)(93)(94)(95)(96).…”
Section: Surgeriesmentioning
confidence: 98%
See 2 more Smart Citations
“…Cosmetic surgeries such as; abdominoplasty, liposuction and breast augmentation (13,68,78-87,69,88-91,70-73,75-77). Organ transplantation complications were reported in ve studies (97)(98)(99)(100)(101). Similarly, bariatric surgery complications were reported in ve studies (92)(93)(94)(95)(96).…”
Section: Surgeriesmentioning
confidence: 98%
“…Five studies reported that, in the case of organ transplantation common complications were infections (e.g. CMV, hepatitis C) (97)(98)(99)(100)(101). The last category was composed of three articles.…”
Section: Postsurgical Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive fungal infection frequently originating at the graft site have been reported in multiple series, including at a rate of 8% from a single center in Oman, of whom 77% underwent nephrectomy. [14,15] Fungal surgical-site infections suggest poor infection control in the operating room. Endemic fungal infections (histoplasmosis, coccidioidomycosis) may be harder to recognize, diagnose, and treat in nonendemic regions.…”
Section: Bacterial Infections Can Include Highly Resistant Organismsmentioning
confidence: 99%
“…The health system in Oman is quite goods is highly recognized by World Health Organization and other various agencies [4,5]. Through the last four decades, a sharp progression in the prevalence of people progressing to ESKD and demanding Renal Replacement Therapy (RRT) has been noticed in Oman [6][7][8][9][10]. The incidence of patients with kidney disease in Oman who received RRT during 1983 was very low (21 per million populations (PMP) and has been gradually increasing (75 PMP in 2001 and 120 PMP in 2013) [11].…”
Section: Introductionmentioning
confidence: 99%